Herd investment decision and savings pattern among lecturers in Nigerian tertiary institutions: The mediating role of financial literacy - Arikewuyo Kareem A; Ariyibi Mayowa E; Folami Rahmon A (Universitas Nusa Cendana, 2026)
Despite relatively high education and income stability, many lecturers in Nigerian tertiary institutions exhibit weak savings outcomes, largely influenced by herd-driven investment decisions and exposure to high-risk informal schemes such as Ponzi operations. Peer influence increasingly shapes their financial choices, raising concerns about the implications for savings behaviour and the role of financial literacy. This study examined the effect of herd investment decisions on savings patterns among lecturers in Nigerian tertiary institutions, with financial literacy serving as a mediating variable. The study adopted a descriptive survey research design and collected primary data from 122 lecturers across tertiary institutions in South-West Nigeria using a structured questionnaire. Herd investment decision, savings pattern, and financial literacy were measured using a four-point Likert-type scale and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings revealed that financial literacy had a positive and statistically significant effect on savings patterns, while herd investment decision also exerted a significant direct effect on savings behaviour. However, herd investment decision did not significantly influence financial literacy, and financial literacy did not mediate the relationship between herd investment decisions and savings patterns. The study concluded that herd investment behaviour influences savings patterns primarily through direct social influence rather than through changes in financial knowledge. While financial literacy independently enhances savings behaviour, it does not mediate the effect of herd behaviour. Therefore, policies aimed at improving savings outcomes should combine financial literacy initiatives with behavioural finance–oriented interventions that address peer influence, social norms, and herd-driven decision-making to promote informed and sustainable saving behaviour among lecturers. Keywords: Investment Herding; Financial Literacy; Savings Pattern; Lecturers; Tertiary Institutions in Nigeria